Bridging the gap between social justice theory and practice : addressing sociopolitical context in trauma therapy with survivors : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Wellington, Aotearoa New Zealand - Dennis, Jessie Anne (Massey University, 2025)
A trauma-informed approach to therapeutic intervention has been adopted across mental health disciplines, including in work with survivors of sexual and interpersonal violence. However, trauma discourses have also been criticised for prioritising medicalised and psychiatric understandings and neglecting the historical, cultural and gender factors which enable and perpetuate violence. Feminist, decolonial and social justice-informed trauma frameworks highlight the need for the sociopolitical contextualisation of trauma within therapy. Increasingly, mainstream ethical and trauma-informed care guidelines also demand that therapists are equipped to explore the sociopolitical factors involved with trauma and distress. However, there is little research about therapists' experiences engaging in such conversations. To bridge the gap between theory and practice, more knowledge is needed about these conversations as they occur in trauma therapy. In this study, a narrative inquiry approach was used to investigate ten therapists’ (psychologists, counsellors and psychotherapists) stories of discussing the sociopolitical context of trauma in therapy with survivors of interpersonal violence. Interviewees told stories that explored how they navigate the inclusion of sociopolitical context in their therapeutic conversations, perceived therapeutic outcomes from these conversations, and what skills, tools and professional and personal learning have been involved. Narrative analysis showed how respondents who were committed to exploring sociopolitical context positioned themselves in resistance to more dominant medicalised trauma narratives, including in their professional training. They outlined the fundamental importance of a relational and power-aware approach, which includes witnessing, collaboratively externalising narratives and being actively non-neutral. Stories described ways in which clients transformed shame and increased their sense of agency through exploring broader social narratives impacting their experience of trauma and healing. Learning in the areas of intersectionality, personal privilege and power was highlighted as necessary to hold these conversations appropriately.
Keywords: social justice, trauma-informed practice, trauma, interpersonal violence, therapy, intersectionality, liberation psychology; 520302 Clinical psychology